Electrochemistry - Khalid, Mohammed A. A. (IntechOpen, 2013)
Electrochemistry has been undergoing significant transformations in the last few decades. It is now the province of academics interested only in measuring thermodynamic properties of solutions and of industrialists using electrolysis or manufacturing batteries, with a huge gap between them. It has become clear that these, apparently distinct subjects, alongside others, have a common ground and that they have grown towards each other, particularly as a result of research into the rates of electrochemical processes. Such evolution is due to a number of factors, and offers the possibility of carrying out reproducible, dynamic experiments under an ever-increasing variety of conditions with reliable and sensitive instrumentation. This has enabled many studies of a fundamental and applied nature, to be carried out.